Shared effects of the clusterin gene on the default mode network among individuals at risk for Alzheimer's disease. (23rd February 2017) - Ye, Qing; Su, Fan; Shu, Hao; Gong, Liang; Xie, Chun‐Ming; Zhou, Hong; Zhang, Zhi‐Jun; Bai, Feng
Summary: Aims: To explore the common effects of the clusterin ( CLU ) rs11136000 variant on the default mode network (DMN) in amnestic mild cognitive impairment (aMCI) subjects and remitted geriatric depression (RGD) subjects. Methods: Fifty‐one aMCI subjects, 38 RGD subjects, and 64 cognitively normal elderly subjects underwent resting‐state fMRI scans and neuropsychological tests at both baseline and a 35‐month follow‐up. Posterior cingulate cortex seed‐based functional connectivity (FC) analysis was used to obtain the DMN patterns. Results: A CLU gene×disease×time interaction for aMCI subjects was mainly detected in the core cortical midline structures of the DMN, and the interaction for RGD subjects was mainly detected in the limbic system. However, they overlapped in two frontal regions, where consistent effects of the CLU gene on FC alterations were found between aMCI and RGD groups. Furthermore, the alterations of FC with frontal, parietal, and limbic regions compensated for episodic memory impairments in CLU ‐CT/TT carriers, while no such compensation was found in CLU ‐CC carriers. Conclusion: The CLU gene could consistently affect the DMN FC with frontal regions among individuals at risk for Alzheimer's disease, and the CLU ‐T allele was associated with more compensatory neural processes in DMN changes.